(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Cellular Manufacturing (CM) is a developed manufacturing philosophy that operates based on the principles of Groups Technology (GT) concept. It used to improve the quality and increase the productivity. Through CM, parts are grouped into families in view of their similarities in design /and or manufacturing features. Then again, machines likewise are gathered into cells to satisfy all the required processes on the families of parts. The integration was done with exam the manufacturing system, for example, job shop before applying the CM. Therefore, in the current paper an attempt was carried out firstly, to evaluate the presented production data, then to integrate the results of this step with the results of the next step, Cell Formation (CF) to acquire an effective CM system. In the evaluation part of the present paper, some hierarchical procedures were applied while in the design (cell formation) section, one of the well- known array based clustering method was utilized, this method known as Rank Order Clustering (ROC) and used to shape cells of machines and families of parts. However, some notable measures were utilized to assess the performance of the proposed CM, these measures are: grouping efficiency GE, grouping efficacy GC, voids, exceptional elements EE, percent of exceptional elements PE and machine utilization MU. To validate this work, three data sets (matrices) were chosen from the open literature. The strategy that followed lead to get a powerful CM solution. The outcomes demonstrated a missing of EE, increasing GE, GC, MU to 92%, 84%, 84% respectively.